A BEME realist synthesis review of the effectiveness of teaching strategies used in the clinical setting on the development of clinical skills among health professionals: BEME Guide No. 61. (2nd June 2020) - Pierce, Cason; Corral, Janet; Aagaard, Eva; Harnke, Ben; Irby, David M.; Stickrath, Chad
Abstract: Background: Literature describing the effectiveness of teaching strategies in the clinical setting is limited. This realist synthesis review focuses on understanding the effectiveness of teaching strategies used in the clinical setting. Methods: We searched ten databases for English language publications between 1 January 1970 and 31 May 2017 reporting effective teaching strategies, used in a clinical setting, of non-procedural skills. After screening, we used consensus to determine inclusion and employed a standardised instrument to capture study populations, methodology, and outcomes. We summarised what strategies worked, for whom, and in what settings. Results: The initial search netted 53, 642 references after de-duplication; 2037 were retained after title and abstract review. Full text review was done on 82 references, with ultimate inclusion of 25 publications. Three specific teaching strategies demonstrated impact on educational outcomes: the One Minute Preceptor (OMP), SNAPPS, and concept mapping. Most of the literature involves physician trainees in an ambulatory environment. All three have been shown to improve skills in the domains of medical knowledge and clinical reasoning. Discussion/conclusions: Apart from the OMP, SNAPPS, and concept mapping, which target the formation of clinical knowledge and reasoning skills, the literature establishing effective teaching strategies in the clinical setting is sparse.